Identification of Architectural Ornaments of Santo Albertus Jetis Church Yogyakarta - Pramudito, Sidhi; Cahyandari, Gerarda Orbita Ida; Arifin, Muhammad Ikhsan (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
Renovation activities can improve quality or even reduce the quality of a building due to the loss of special elements in the building. One of the element in a building that can give special features to an architectural work is ornament. The aim of this study was to identify ornamental design principles that can be found in several works of Mangunwijaya and their application to the buildings of the Santo Albertus Church in Jetis Yogyakarta. This research using descriptive methods through case studies in the field with analysis through qualitative methods. The methods of retrieving data through direct observation and documentation and supported by literature studies. The results of this study indicate that the ornaments on the Santo Albertus Church has flora and fauna motifs that are made in a combination style and have a style of contemporary ornaments, and the ornaments that are made have a propensity to affect the spirit of the space. Based on these results, it is expected to be a suggestion and consideration for the renovation activities that are currently being carried out, especially in understanding the use and meaning of the ornament, so the building of the Church of Santo Albertus Jetis did not lose the identity.Â DOI:Â https://doi.org/10.26905/lw.v11i2.2930